2021
DOI: 10.1016/j.ccc.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Treatments for Acute Respiratory Distress Syndrome

Abstract: Acute respiratory distress syndrome is a heterogenous syndrome with many etiologies for which there are no definitive pharmacologic treatments, despite decades of research. We explore some adjunctive pharmacologic therapies, including neuromuscular blockade, corticosteroids, and inhaled pulmonary vasodilators. Additionally, we explore some investigative therapies, including Vitamin C, beta-agonists, statins, mesenchymal stromal cells, and granulocyte–macrophage colony stimulating factor. We do discuss the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…The activation of inflammatory processes and the involvement of inflammatory factors further promote the development of ARDS [ 21 ]. At present, the mortality rate of ARDS is still high, and timely and effective treatment measures can improve the prognosis of patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of inflammatory processes and the involvement of inflammatory factors further promote the development of ARDS [ 21 ]. At present, the mortality rate of ARDS is still high, and timely and effective treatment measures can improve the prognosis of patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two reviews summarized pharmacological treatments for patients suffering from ARDS [ 232 , 233 ]. Although, the main message of both reviews is that there is no appropriate pharmacological therapy option, but only supportive care, they agree on the necessity to subgroup ARDS patients to identify personalized treatment concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Although research on ARDS has been conducted for decades, no effective treatment has been found yet. Supportive care measures based on respiratory support are still used in clinical practice [ 59 ]. This is also true for high-altitude ARDS.…”
Section: Treatmentmentioning
confidence: 99%